Optimizing Healthcare and Financial Systems: A Technical Guide for Building Scalable, Reliable Platforms - Sachin Telalwar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the implementation strategies for building scalable and reliable platforms in healthcare and financial systems. The article addresses critical aspects of modern system architecture, including microservices implementation, fault tolerance mechanisms, data security protocols, and performance optimization techniques. Through analysis of real-world implementations across both sectors, the guide presents practical approaches to achieving system reliability while maintaining regulatory compliance. The article examines the evolution of cloud-native solutions, distributed systems, and emerging technologies such as blockchain and artificial intelligence, providing insights into their impact on system architecture and performance. The article particularly focuses on the integration of advanced monitoring solutions, user-centric design principles, and continuous improvement methodologies that enable organizations to build and maintain robust platforms capable of handling increasing transaction volumes while ensuring data security and user satisfaction.